2020
DOI: 10.1111/dme.14348
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of spontaneous, user‐generated data about gestational diabetes on online forums: implications for diabetes prevention

Abstract: Aims To explore the experiences and perceptions of gestational diabetes mellitus reported by women within online parental-support forums and, specifically, to analyse what women say about a diagnosis of gestational diabetes, their future risk of type 2 diabetes, and lifestyle behaviour for management of gestational diabetes and prevention of type 2 diabetes. Methods The discussion boards of two parenting websites (Mumsnet and Netmums) were searched using the search term 'gestational diabetes or GD' in February… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
2
8
0
2
Order By: Relevance
“…Although there may have been some variations in provision of care to women with GDM between the Health Boards, their views and experiences surrounding the topic seemed fairly consistent. They also chimed well with findings from other studies in a variety of settings, which suggest that many women with GDM, for various reasons, do not recognise the serious long-term implications of their GDM diagnosis [4][5][6][7][8]. Our findings respond to the recognition that a shift in perception of GDM is needed [13], from one where it is assumed to be a treatable short-term condition, to one that has the potential to influence the long-term health of mothers and their children in the future.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although there may have been some variations in provision of care to women with GDM between the Health Boards, their views and experiences surrounding the topic seemed fairly consistent. They also chimed well with findings from other studies in a variety of settings, which suggest that many women with GDM, for various reasons, do not recognise the serious long-term implications of their GDM diagnosis [4][5][6][7][8]. Our findings respond to the recognition that a shift in perception of GDM is needed [13], from one where it is assumed to be a treatable short-term condition, to one that has the potential to influence the long-term health of mothers and their children in the future.…”
Section: Discussionsupporting
confidence: 77%
“…While reduced risk of T2D after GDM has been documented in women who have successfully made improvements to diet and physical activity levels post-delivery, effective interventions within heath care settings to achieve this are intensive and costly [ 4 ]. We have recently completed qualitative research that has identified that there are illness perceptions surrounding GDM that, if they are not addressed, are likely to compromise the effect of lifestyle interventions [ 5 , 6 ]. For example, although many women know that there is an association between GDM and T2D, they may not perceive themselves personally as being at increased risk.…”
Section: Introductionmentioning
confidence: 99%
“…Although there may have been some variations in provision of care to women with GDM between the Health Boards, their views and experiences surrounding the topic seemed fairly consistent. They also chimed well with ndings from other studies in a variety of settings, which suggest that many women with GDM, for various reasons, do not recognise the serious long-term implications of their GDM diagnosis [3][4][5][6][7] . However, we used an opt-in convenience sampling, so we cannot be sure how widespread the views of our participants were, nor whether those HCPs who opted in were those with particularly strong views or an interest in the topic.…”
Section: Discussionsupporting
confidence: 73%
“…We have recently completed qualitative research that has identi ed that there are illness perceptions surrounding GDM that, if they are not addressed, are likely to compromise the effect of lifestyle interventions 4,5 . For example, although many women know that there is an association between GDM and T2D, they may not perceive themselves personally as being at increased risk.…”
Section: Introductionmentioning
confidence: 99%
“…Information was accessible at all times and could be informative and supportive, but many users raise doubts about trustworthiness [42,44,45]. A recent analysis of posts on Mumsnet and Netmums forums concluded that the support provided does not encourage T2DM prevention because diabetes risk was rarely discussed and users downplayed the seriousness of GDM and its association with lifestyle behaviours [46]. Instead of searching for such groups themselves, mothers could be directed to reliable resources by a trusted professional or body.…”
Section: Implications For Practicementioning
confidence: 99%